Journal of the Relationship Between Social Support and Achievement Motivation in High School Students - Juan Bobby Arief Nugraha Juha; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2021)
Achievement motivation is a determinant of student achievement, students should have high achievement motivation regardless of the circumstances, when motivation for achievement is low, it will affect student achievement. Therefore it is necessary to look for factors that influence achievement motivation. This study aims to determine the relationship between social support and achievement motivation and how much influence social support has on achievement motivation on students at the AL-Islam Krian High School Sidoarjo. This research was conducted with a quantitative correlational research method, using proportional sampling. with a sample of 382 students. The measurement tool uses two scales, namely social support scale and achievement motivation scale using the Spearman product moment correlation technique with the help of IBM Statistics 20 Version for Windows. The results of the analysis show that there is a relationship between social support and achievement motivation. The implication of this research is to develop student achievement and provide interventions to improve the quality of education. Increasing the quality of education to the maximum can increase social support and achievement motivation in students.